Crisis Communication of the Prosperous Justice Party in the 2024 Jakarta Gubernatorial Election - Muhamad Agung Dharmajaya; Aminah Swamawati (Ikatan Sarjana Komunikasi Indonesia, 2026)
Partai Keadilan Sejahtera (PKS) faces crucial challenges in managing political communication crises arising from the dynamics of gubernatorial candidacy. The purpose of this study is to analyze the crisis communication strategies of PKS during the 2024 Jakarta gubernatorial election. This study employs a descriptive method with a qualitative approach. The findings indicate that PKS encountered significant challenges in managing public perceptions regarding its responsibility in various issues surrounding the 2024 Jakarta gubernatorial nomination. The level of perceived responsibility among the public is influenced by the source of the crisis and the party's initial response, while previous crisis history also shapes public perception. PKS's relationship with its urban Muslim supporter base serves as an important social capital, although communication challenges with other groups remain. In response to the crisis, PKS implemented denial, diminish, and rebuild strategies, with the rebuild strategy emerging as the key to reputation recovery through direct communication, the nomination of candidates with integrity, and the implementation of concrete programs. The combination of effective crisis situation management and well-applied response strategies has enabled PKS to maintain political stability and enhance public trust.